0600 Impact of Group-Based Sleep Apnea Management Intervention on Patient Reported Outcomes in Patients on Positive Airway Pressure for Obstructive Sleep Apnea. (27th April 2018) - Syed, M; Kinzy, T G; Mehra, R; Moul, D E; Vanek, R; Campean, T; Foldvary-Schaefer, N; Walia, H K
Abstract: Introduction: Behavioral interventions are used with varying success to improve positive airway pressure (PAP) adherence in patients with obstructive sleep apnea (OSA) with an overarching goal of improving patient reported outcomes (PROs). We hypothesize group-based intervention, the Sleep Apnea Management (SAM) clinic will improve the PROs on patients already on PAP for OSA. Methods: SAM clinic visits from 2015–16 were retrospectively analyzed in 235 patients. PROs include Patient Health Questionnaire (PHQ-9) (n=112), PROMIS global mental (n=114), and physical health (n-112), Functional Outcomes of Sleep Questionnaire (FOSQ) (n=62), Fatigue Severity Scale (FSS) (n=148), and Epworth Sleepiness Scale (ESS) (n=145). Measures most proximate to SAM clinic visits were collected within 180 day interval. Difference in PROs were calculated pre and post SAM clinic using paired-samples t-tests (mean and standard deviation). Improvement was defined for each scale based on minimal clinically important difference (MCID), if available, or a half standard deviation change in those with abnormal baseline scores; PHQ-9 (n=74), PROMIS global mental (n= 49) and physical health (n=65), Functional FOSQ (n=3), FSS (n=101), and ESS (n=64). Results: Patients were age 57.1(SD 12.3) years, 74.5% white, 55.7% male, with a median body mass index (BMI) of 34kg/m 2 . Statistically significant improvements in ESS and FSS scores were found, with mean differences of -1.52 (95% CI -2.10, -0.93) and -2.88 (95% CI -4.73, -1.03) respectively. PHQ-9, PROMIS mental and physical health, and FOSQ scores did not change significantly. Of those with abnormal pre SAM PRO's scores, improvement to MCID was observed as: PHQ9-25.7%, PROMIS global mental 16.3%, PROMIS global physical 20%, FOSQ 0%, FSS 36.6%, ESS scores 54.7%. Conclusion: Significant improvement was observed in ESS and FSS with the group-based SAM clinic intervention with more pronounced and universal improvements noted in those with abnormal baseline PRO values, thereby supporting the benefit and utility of the SAM clinic. Support (If Any): We acknowledge The Cleveland Clinic's Knowledge Program Data Registry and Neurological Institute Center for Outcomes Research and Evaluation (NICORE) for data and biostatistical resources.